STATE OF THE ART OF PSYCHOMOTOR EDUCATION AT THE PRESCHOOL LEVEL IN THE COMMUNE OF PORTO-NOVO IN BENIN - Yakoubou, M. Sawab; EDOH, K. Pierrot; Messan, Folly; Tito, Albérick; LAWANI, MOHAMED MANSOUROU (My University, 2022)
Context: In general, well-conducted psychomotor activities promote harmonious development and have a positive impact on children's health. These activities also condition the acquisition and improvement of the child's global motor skills. In the Commune of Porto-Novo, incomplete motor skills are observed among primary school children in both the public and private sectors. This is why the present study aims to investigate the causes of this observation in kindergarten in order to propose approaches to remedy it. Materials and Method: Twenty-seven (27) teachers from both public kindergartens with at least 100 pupils (15) and private kindergartens with at least 70 pupils (12) were randomly selected. They were grouped according to spontaneous, hidden and evoked interventions. Spontaneous and hidden interventions represent practices that are not conducive to children's psychomotor development, whereas evoked intervention was found to be the best option for promoting children's psychomotor development. Data were collected through individual semi-directive interviews and open observation in the classrooms. These data were analyzed and the percentages were compared. Results: Only 8 teachers (29.63%) practiced an evoked intervention. However, 19 teachers (70.37%) practiced either spontaneous (11) or covert (8) intervention. The comparison of these observed percentages shows a significant difference (p<0.05) at the 5% risk. Conclusion: The incomplete achievements observed at the primary level are due to the lack of space, and teaching materials and especially to the lack of knowledge of the concept of psychomotricity and its implications. Initial training that deviates from these requirements does not seem to be conducive to the harmonious psychomotor development of kindergarten children.
Keywords: psychomotor development; preschool education; educational program; Porto-Novo